Atypical presentation of neurofibromatosis type 1 in a 10-month-old girl: a case report - Asad, Marui; Zahra, Fatima Al-; Pandit, Gauri Shankar; Ahmad, Rafi Raza; Awais, Muhammad; Akhtar, Nadeem (International Journal of Contemporary Pediatrics, 2022)
Neurofibromatosis type 1 (NF1) is a neurocutaneous genetic disorder of heterogenic symptoms majorly affecting the nervous system, eye, skin and bone. This study was about a 10-month-old female child who developed a lump/mass on the left side of neck 3 months ago that rapidly increased in size along with ulceration and bleeding for one month with no associated symptoms. MRI of neck showed large heterogeneous and enhancing lesion with thick lobulated folds noted posteriorly, located in the left posterior cervical space deep to the sternocleidomastoid muscle. On histopathological examination nerve sheath tumor favoring NF1 was confirmed. Child underwent debulking/excision of the mass.